DEFORMASI INTERAKSI DUA PAKET GELOMBANG DARI PERSAMAAN IMPROVED KdV (IKdV - Sutimin, Sutimin (MATEMATIKA, 2006)
Here, We will study the nonlinear two waves packet interaction. The two waves packet is modeled by Improved Koreteweg de-Vries (IKdV) equation. The primary amplitudes are modulated by two-soliton of the nonlinear SchrÅ‘dinger (NLS) equation. In this paper, we analyzed the interaction patterns of the two waves packet at the peak interaction. We have shown here, that during under going to the interaction region, the deformation of amplitudes profile will be occurred. The large deformation is characterized by the ratio of the amplitudes parameter and the wave numbers of each wave packets. The symmetry interaction also can be analyzed by the characterization of the parameters.